KETAHANAN PANGAN RUMAH TANGGA PETANI SAWAH DI WILAYAH ENCLAVE TAMAN NASIONAL BUKIT BARISAN SELATAN - Amirian Amirian; Yayuk Farida Baliwati; Lilik Kustiyah (Jurnal Gizi dan Pangan, 2008)
The aim of this research was to know the food security of farmer household, based on the availibility of staple food, access to food and  utilization of food of farmer household. The research design was cross-sectional study. The samples were consisted of 35 owner farmer, 12 yeoman, and 13 farmworker.Primary and secondary data was analyzed by Microsoft Excel and SPSS version 13 for windows. The result showed that 48.33% of husband and 78.33% of wife were <40 years old. As many as 66.67% ofhusbandeducationand70.00% of wife education were elementary school.  Mostofthesamplewere farmers, 26.67% husband and 18.33% wife had additional work. The result showed,based on the availability of staple food, 70.00% of household catagorized as food secured. Based on the access to food, 65.00% of household catagorized as food secured, and based on the utilization of food, 56.70% of household catagorized as food secured. The conclusion of this research, 63.30% of household catagorized as food secured based on combination of three component of food security. There was a significant positive correlation (p<0.01) betwen income per household per month, family size, access to clean water, total of rice production, and the rice production distributed to household with the availability of energy per capita per day.